Cleavage of Grb2-Associated Binding Protein 2 by Viral Proteinase 2A during Coxsackievirus Infection - Deng, Haoyu; Fung, Gabriel; Qiu, Ye; Wang, Chen; Zhang, Jingchun; Jin, Zheng-Gen; Luo, Honglin (Frontiers in Cellular and Infection Microbiology, 2017)
Coxsackievirus type B3 (CV-B3), an enterovirus associated with the pathogenesis of several human diseases, subverts or employs the host intracellular signaling pathways to support effective viral infection. We have previously demonstrated that Grb2-associated binding protein 1 (GAB1), a signaling adaptor protein that serves as a platform for intracellular signaling assembly and transduction, is cleaved upon CV-B3 infection, resulting in a gain-of-pro-viral-function via the modification of GAB1-mediated ERK1/2 pathway. GAB2 is a mammalian homologue of GAB1. In this study, we aim to address whether GAB2 plays a synergistic role with GAB1 in the regulation of CV-B3 replication. Here we reported that GAB2 is also a target of CV-B3-encoded viral proteinase. We showed that GAB2 is cleaved at G238 during CV-B3 infection by viral proteinase 2A, generating two cleaved fragments of GAB2-N1-237 and GAB2-C238-676. Moreover, knockdown of GAB2 significantly inhibits the synthesis of viral protein and subsequent viral progeny production, accompanied by reduced levels of phosphorylated p38, suggesting a pro-viral function for GAB2 linked to p38 activation. Finally, we examined whether the cleavage of GAB2 can promote viral replication as observed for GAB1 cleavage. We showed that expression of neither GAB2-N1-237 nor GAB2-C238-676 results in enhanced viral infectivity, indicating a loss-of-function, rather than a gain-of-function of GAB2 cleavage in mediating virus replication. Taken together, our findings in this study suggest a novel host defense machinery through which CV-B3 infection is limited by the cleavage of a pro-viral protein.